Simulation of Bipolar Charge Transport in Graphene by Using a Discontinuous Galerkin Method (Communications in Computational Physics, 2019)
Charge transport in suspended monolayer graphene is simulated by a numerical deterministic approach, based on a discontinuous Galerkin (DG) method, forsolving the semiclassical Boltzmann equation for electrons. Both the conduction andvalence bands are included and the interband scatterings are taken into account.The use of a Direct Simulation Monte Carlo (DSMC) approach, which properlydescribes the interband scatterings, is computationally very expensive because the valence band is very populated and a huge number of particles are needed. Also the choiceof simulating holes instead of electrons does not overcome the problem because thereis a certain degree of ambiguity in the generation and recombination terms of electron-hole pairs. Often, direct solutions of the Boltzmann equations with a DSMC neglectthe interband scatterings on the basis of physical arguments. The DG approach doesnot suffer from the previous drawbacks and requires a reasonable computing effort.In the present paper the importance of the interband scatterings is accurately evaluated for several values of the Fermi energy, addressing the issue related to the validityof neglecting the generation-recombination terms. It is found out that the inclusion ofthe interband scatterings produces huge variations in the average values, as the current, with zero Fermi energy while, as expected, the effect of the interband scatteringbecomes negligible by increasing the absolute value of the Fermi energy.